Ex Libris V. M. Yuste / F. S. - Saez, Julio Fernandez (1924- ). ([wydawca nieznany], 1960)
Siedzący na liściu żuk, napis: Ex Libris V. M. Yuste. Sygnatura artysty i nr dzieła: 175 w obrębie kompozycji.